EFEKTIVITAS PELAKSANAAN PERATURAN PENCATATAN PERCERAIAN DI KANTOR URUSAN AGAMA - Fatahuddin Aziz Siregar, Juriyana Megawati Hasibuan dan (IAIN Padangsidimpuan, 2020)
Marriage is a sacred bond which is ideally only held once in a lifetime. Both Islamic law and positive law require an eternal happy marriage. To support this the Koran proclaims marriage as mitsaqan galiza. The marriage is then registered in the state administration. In line with this, the laws and regulations are formulated in such a way as to make divorce more difficult. However, when there are acceptable reasons and due to coercive conditions, divorce can be done through a judicial process. The divorce must then be registered by taking certain procedures. The court delivered the notice and sent a copy of the decision to the marriage registrar to file the divorce properly. The implementation of this divorce record was not effective. The separation of the Religious Courts Institution from the Ministry of Religion has become a factor that causes the registration task not to be carried out. The loss of the obligation to submit a copy of the decision on the judge's ruling caused the recording to be constrained. The unavailability of shipping costs also contributed to the failure to register divorce. Even though there is a threat to the Registrar who neglects to deliver a copy of the verdict, unclear sanctions make this ineffective. As a result of the lack of recording of divorce, the status of husband and wife becomes unclear and opens opportunities for abuse of that status.